(untitled) (Web of Teachers: Inderscience Research, 2024)
We need to recognize that the family is the center of education that ensures the eternity of life, the continuity of generations, preserves our sacred traditions, and at the same time, has a direct impact on how future generations will become human beings. A child lives in a family environment from the day of birth.